A 3D-model for O2 airglow perturbations induced by gravity waves in the upper mesosphere - Li, Anqi (My University, 2017)
To investigate the influence of atmospheric waves in the mesosphere, a new Swedish satellite MATS (Mesospheric Airglow/Aerosol Tomography and Spectroscopy) will be launched in 2019. It will observe infrared emissions at 762 nm from the O2(b1+ g ) airglow in the region of 70 - 110 km altitude. As a part of the design work for the MATS project, an accurate forward model is needed to estimate what MATS is expected to measure. The results from this model will be used to evaluate the retrieval methods for processing the measurements from MATS. In this thesis project, a gravity wave model and a photochemistry model were coupled to simulate both the day- and nightglow emission fields in three spatial dimensions and time. Simulated satellite images were generated taking into consideration the sphericity of the Earth and the limb-viewing geometry of MATS. Simulation parameters were set according to the preliminary design of the instrument, such as the satellite orbit, image resolution and spectral selections. These satellite images were the first simulated airglow limb images made for the MATS project. By analysing the output data, the relations between wave parameters and airglow perturbations were investigated. It was shown that wave patterns can be easily observed between 85 - 105 km due to the relatively large perturbation in airglow emissions. The O2 airglow emission field was found to be highly sensitive to atomic oxygen concentration field as an input. Furthermore, as expected, wave patterns projected on simulated satellite images largely depend on the horizontal orientation of the wave propagation. This implies that a tomographic reconstruction is needed when the angle between the wave front and the limb-viewing direction is large. Finally, limitations of the model were discussed.
Keywords: Geovetenskap och miljövetenskap; Earth and Related Environmental Sciences